Characterization of Sputter Deposited Molybdenum Thin Film on PET for Wearable Health Sensor - Nga, Ji Xuan; Ali, Ahmad Hadi (Enhanced Knowledge in Sciences and Technology, 2026)
Wearable health sensors (WHS) consist of strain sensors that need to have flexible conductive materials that can withstand mechanical stress. The inadequate of contact can lead to signal corruption and or false signal in a WHS. This study aims to optimize the best parameter for sputtering for molybdenum (Mo) thin films deposited on polyethylene terephthalate (PET) substrates. Mo was used because of its conductivity and mechanical stability, meanwhile PET is chosen as substrate in this study because of its flexibility for strain sensors. This study also explores the characterization of Mo thin films deposited on PET substrate with reference to their topological, morphological, optical, electrical and mechanical strain properties. A direct-current (DC) sputtering system was used to deposit Mo films with different deposition times which are 3, 6, 9, 12, 15 and 18 minutes. Characterization such as Ellipsometry, Atomic Force Microscopic (AFM), Electron Microscopic (SEM), UV–Visible (UV–Vis) spectroscopy, Four-Point Probe and mechanical strain test was carried out to determine the best sputtering parameter for Mo thin films on PET. The findings reveal that the thicker Mo thin films on PET of 10.0 and 10.6 nm enhances continuity of films and minimizes roughness of surfaces that improves the stability of the electrical performance. In general, the Mo/PET films have appropriate properties to be incorporated into the flexible wearable health sensors, with its capacity to be conductive, mechanically strong, and uniform. These results give a basis to the continued implementation of flexible electronic devices such as wearable health sensors.